Pengaruh Store Atmosphere, Product Quality, dan Price Discount terhadap Impulse Buying pada Gerai Miniso: Studi pada Konsumen Gerai Miniso Royal Plaza Surabaya - Fanza Shofaun Nafsi; Prabowo, Budi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Impulse buying often occurs solely based on the emotions that consumers feel at the time of purchase. Impulse buying is one of the factors that retailers or manufacturers pay attention to increase revenue. Factors that can influence impulse buying towards a retail store include store atmosphere, product quality and price discounts. Miniso creates impulse buying in each of its outlets with an attractive store appearance, provides quality products, and always runs promotional programs that encourage consumers to impulse buy. The aim of this research is to analyze and find out more about the influence of store atmosphere, product quality and price discount simultaneously and partially on impulse buying among Miniso consumers at Royal Plaza Surabaya. The type of research used is associative research with a quantitative approach. The population of this research is consumers of Miniso outlets at Royal Plaza Surabaya. The sample in this study used 100 respondents. With a purposive sampling technique. The research data collection technique uses a questionnaire. The data analysis technique uses multiple linear regression analysis. The results of this research show that store atmosphere, product quality and price discount simultaneously influence impulse buying. However, partially there is no significant influence between store atmosphere on impulse buying. Meanwhile, product quality and price discount partially influence impulse buying.